Fenomena Katarsis Mengenai Kesehatan Mental pada Media Sosial Tiktok (Studi Kasus pada Akun Tiktok @Userpenmat0y) - Laksmi Chyntia Dewi; Wiwik Novianti; Wisnu Widjanarko; Agoeng Noegroho; Santoso (Syntax Idea)
The aim of this research is to educate the public in using social media wisely and understand issues regarding mental health that occur on social media, especially on Tiktok, so that people understand the cathartic phenomenon regarding mental health on Tiktok social media. The type of research used is qualitative research with a case study method, where the researcher conducted research by observing and interviewing the owner of the Tiktok account @userpenmat0y and observing several examples of cathartic Tiktok video content about mental health on the account by taking three (3) pieces of content. has the highest number of views, likes and comments compared to other uploaded content. The result of this research is that by looking at examples of uploaded content about mental health, it can explain a little about the phenomenon of catharsis and its impacts, both negative and positive, in terms of the account owner or content creator as well as in terms of other TikTok users who also commented on the upload.